Caro valdininkų požiūris į lietuviškosios spaudos draudimą - Vėbra, Rimantas (Knygotyra, 1972)
The policy of ruling circles of the Russian empire in Lithuania has not yet been thoroughly studied in the Lithuanian historiography. Attention has been concentrated on the activity of extreme reactionaries supporting violence. The article, based on the new archival documents and little known printed sources, deals with the attitude of more liberal officials to the interdict of the Lithuanian written language, which was the main issue in the Lithuanian national movement in the second half of the 19th century. On the basis of facts periods of reaction and liberalism have been singled out at the end of the article. An analysis of the activity of the liberal officials gives us fuller idea of the historical conditions in which the Lithuanian nation was being formed.